The relationship between isokinetic strength and jump performance in elite female volleyball players - Uslu, S.; Abazovic, E.; Cauševic, D.; Mahmutovic, I.; Riza, B. (Acta Kinesiologica, 2021)
The purpose of this study was to evaluatethe relationship between knee extensor and flexor muscles strength and vertical jump in professional female volleyball players. Forty-one female volleyball players participated in this study. Isokinetic PT and was measured at 60°/s, whilst CMJ performance using a force plate. The participants were later divided to WG (weaker group -PT/BW<2) and SG (stronger group -PT/BW>2). Isokinetic concentric knee extension and flexion PT was significantly correlated with CMJ performance. However, higher correlation coefficients were obtained at the non-dominant leg. No significant differences were found but mere trend favoring non-dominant leg muscles in the weaker group. Strong positive correlation exists between isokinetic knee PTand CMJ height in professional female volleyball players. When divided and compared to WG and SG the results indicate weaker players tend to modify their technique individually and towards unilaterality as so they could maximize their performance